Changes in left ventricular function after spontaneous coronary artery dissection - Franco, Christopher (Clin Cardiol, 2017)
BACKGROUND: Spontaneous healing of spontaneous coronary artery dissection (SCAD) and left ventricular ejection fraction (LVEF) recovery is frequently observed clinically. However, LVEF on presentation and follow‐up imaging has not been described. HYPOTHESIS: We hypothesize that LV dysfunction improves at follow‐up after initial SCAD presentation. METHODS: We included patients with nonatherosclerotic SCAD prospectively followed at Vancouver General Hospital, who had baseline assessment of LVEF and wall‐motion abnormality (WMA) during their index presentation. A subset of these patients had repeat assessment of their ventricular function at follow‐up. We compared the baseline LVEF and WMA with follow‐up assessments and correlated to long‐term cardiovascular outcomes. RESULTS: We included 277 SCAD patients who had baseline ventricular assessment performed. The average age was 52.4 ± 9.4 years, and 90.3% were female. All presented with myocardial infarction (24.2% STEMI, 75.8% NSTEMI). At baseline, the mean LVEF was 55.6% ± 9.1% and 72/277 (26.0%) had LVEF <50%. The presence of WMA was observed in 237/277 (85.6%) cases. Of 164 patients with repeat assessments, the baseline LVEF was 54.6% ± 9.2%, with improvement to 60.7% ± 7.2% at follow‐up (P < 0.001). Baseline LVEF of <50% was observed in 29.9%, but only 6.7% had LVEF <50% at follow‐up (P < 0.001). Baseline WMA was observed in 87.2% but decreased to 44.5% at follow‐up (P < 0.001). Multivariable analysis showed that presentation with STEMI (odds ratio [OR]: 2.71, P = 0.001), troponin I >50 µg/L (OR: 1.02, P = 0.005), and SCAD involvement of the LAD (OR: 2.5, P = 0.002) were independent predictors of baseline LVEF <50%. CONCLUSIONS: In our large, prospectively followed SCAD cohort, the majority of patients presented with WMA and had relatively normal LVEF. Over half had subsequent normalization of WMA and LVEF on follow‐up assessment.